Design Strategies for Façade integrated Photovoltaic Technology (FiPV) - Mariam Ahmad; Hina Zia (Proceedings of the International Conference of Contemporary Affairs in Architecture and Urbanism-ICCAUA)
The rapid pace of urbanisation has caused a surge in the energy demand, thus emphasizing the need for Net Zero Energy buildings. A plethora of financial and non-financial incentives for promoting energy efficient and renewable energy buildings are being offered by several local governments in India. Policies have favoured the inclusion of photovoltaic technology within the buildings. Despite the efforts, adoption of the technology within the envelope is quite restrictive. The photovoltaic technology is either added onto the rooftops or provided as double façade. The concept of replacing the building skin with this technology has not been explored enough. This paper attempts to propose a framework, for designing a photovoltaic façade, replacing the conventional building skin. It has tried to address some of the barriers, and inhibitors in uptake of the technology. It explores provision of an assessment framework for envelope performance of photovoltaic facade.